Identification of nuclear factor YA6 genes in sorghum and characterization of their involvement in drought tolerance - Wu, GuoJiang; Wang, ZhenGuo; Li, Yan; Du, PinTing; Liu, XinYu; Hou, Jie; Zhou, Wei; Zhou, YaXing (Frontiers in Plant Science, 2025)
Nuclear factor Y alpha proteins (NF-YAs) are conserved transcription factor proteins crucial to plant growth and development that exhibit specific responses to biotic and abiotic stresses. Using bioinformatics approaches to investigate the NF-YA family in sorghum (Sorghum bicolor), we identified nine SbNF-YA genes unevenly distributed on four of the 10 sorghum chromosomes. Despite variations in gene structure, all encode proteins have the characteristic CBFB_NFYA domain and other predicted motifs. The secondary structure of SbNF-YA members is predominantly composed of α-helices and random coils. A phylogenetic analysis of NF-YAs of sorghum and other plant species indicated that SbNF-YAs are closely related to NF-YAs from maize (Zea mays) and distantly related to those in Arabidopsis (Arabidopsis thaliana). A colinearity analysis determined that six of the nine SbNF-YA genes arose from segmental duplication events. Transcriptome and RT-qPCR analyses showed that the expression levels of eight of the SbNF-YA genes (SbNF-YA5 being the exception) are responsive to drought stress to varying degrees. Notably, SbNF-YA1, SbNF-YA4, SbNF-YA6, SbNF-YA8, and SbNF-YA9 expression was significantly upregulated under the stress conditions, suggesting that they participate in drought response. When heterologously expressed in Arabidopsis, SbNF-YA6 conferred greater tolerance of drought stress imposed by treatment with the osmolyte mannitol, with the transgenic Arabidopsis lines showing superior germination rates; longer roots; higher fresh weight; higher activities of the enzymes peroxidase, superoxide dismutase, and catalase; and higher soluble protein and proline contents, compared to the wild type. Additionally, the transgenic Arabidopsis lines accumulated lower levels of hydrogen peroxide, superoxide anion, and malondialdehyde. The expression levels of several drought-responsive genes were elevated in transgenic Arabidopsis seedlings relative to the wild type, indicating that the heterologous expression of SbNF-YA6 enhances the drought tolerance of Arabidopsis.